Tratamento combinado de lixiviado de aterro sanitário e esgoto doméstico utilizando ozônio - Schons, Alisson (Universidade do Vale do Rio dos Sinos, 2016)
Landfill leachate has been characterized by the high concentration of recalcitrant organic matter, ammoniacal nitrogen and toxic compounds. Recalcitrant organic compounds are rarely removed by traditional effluent treatment processes. In addition, the treatment of the leachate is colloquial to meet the discharge standards of the effluent. Likewise, the domestic sewage disposal generated by the communities also needs previous treatments to avoid impacts on the environment. Due to the characteristics of domestic sewage, with low concentrations of organic carbon in relation to the leachate, it has allowed the combined treatment of these effluents to be a viable alternative. In view of this situation, this work had the objective of evaluating the combined treatment of domestic sewage of (ETP) and the raw leachate of the San Leopoldo landfill using ozone (O3) as an oxidizing agent. Three batch trials were carried out with a scheduled duration of five hours and three trials lasting two hours, with different yields of O3 of 8.9, 9.6 and 10.5 g of O3.h-1, applied to the mixture Of 2% of landfill leachate) For domestic sewage (2L of LAS and 158L of sewage). Each assay was performed in duplicate and the following parameters were monitored: Oxygen Chemical Demand, Biochemical Oxygen Demand, Apparent and True Color, Turbidity, pH and calculated O3 utilization and loss rates. The results showed that the treatment with O3 can be an excellent alternative of pretreatment of effluents, obtaining average removals of COD, BOD, CA, CV and Turbidity of up to 46%, 51%, 86%, 86% and 81 % Respectively. Average test and removal hours of up to 23%, 48%, 78%, 76% and 58%, respectively, in two hours of testing. The highest removal rates were obtained in the tests with higher flows of O2 and yields of O3 and in the first two hours of the test. It was only possible to meet the effluent release standards required by current legislation, in trials with a duration of five hours and with the highest production of O3 and O2. The treatment system also contributed to an improvement in the biodegradability of the effluent if the BOD/COD ratio was analyzed. As for the rates of use and loss of O3, it was verified that the highest amount of O3 occurred for the parameters indicative of organic matter and for the tests with lower production of O3. The higher the O3 production, the higher the O3 loss and the greater oxidant loss may have been due to volatilization in the effluent accumulation reservoir, since there was no gas loss due to Off-gas and the method used Not Detected The residual ozone.
Keywords: Lixiviado; Processo oxidativo avançado; Ozônio; Leachate; Advanced oxidation process; Ozone; ACCNPQ::Engenharias::Engenharia Civil